Excess mortality among kidney transplant recipients: Impact of COVID-19-related deaths during the pandemic - Cristelli, Marina Pontello; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Pereira, João Filipe Costa Alves; Taddeo, Julia Bernardi; Viana, Laila Almeida; Requião-Moura, Lucio Roberto; Chow, Charles Yea Zen; Nakamura, Monica Rika; Tedesco-Silva, Helio; Medina-Pestana, José (Wiley, 2024)
Background: Because COVID-19 has been associated with high lethality rates among kidney transplant recipients (KTR), but also with a severe disruption and delays in overall healthcare, this study aims to evaluate the excess mortality in the pandemic era among KTR in a high-volume Brazilian transplant center. Methods: This study used data from a single center that provides follow-up on all its transplant recipients. The population of interest included all the patients who were transplanted between August 31, 1983 and December 31, 2022 and who were live from January 1, 2014. Using the “AutoRegressive Integrated Moving Average” forecasting algorithm, the expected mortality for the pandemic era (2020–2022) was modeled from the pre-pandemic era (2014–2019). Results: There were 12 077 KTRs at risk of dying in the entire observation period. In the pre-pandemic era, there were 21 deaths per 1000 patients at risk. In the pandemic era, there were 1429 observed deaths (rate of 47 deaths per 1000 patients at risk) versus the expected 587 deaths, resulting in an absolute number of 842 excess deaths, or an observed-to-expected ratio of 2.4, or an absolute rate of 26 deaths in excess per 1000 patients at risk. The excess deaths exhibited a temporal pattern mirroring that of the surges in new cases and lethality rates of COVID-19. COVID-19-related deaths drove 94% of excess mortality in the pandemic era. Conclusion: In this large cohort of KTR under centralized follow-up, more than twofold excess mortality was primarily driven by COVID-19-related deaths, highlighting the vulnerability of this population to the most severe presentation of SARS-CoV-2 infection. (Figure presented.).
Keywords: COVID-19; excess mortality; kidney transplant